2010
DOI: 10.1016/j.cub.2010.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Relocation of the Chromosomal Passenger Complex Prevents Mitotic Checkpoint Engagement at Anaphase

Abstract: The mitotic checkpoint monitors the attachment of kinetochores to microtubules and delays anaphase onset until all sister kinetochores have become attached to opposite poles [1, 2]. Correct bipolar attachment leads to kinetochore deformation and tension and satisfies the checkpoint [3-6]. What prevents mitotic checkpoint reactivation when sister centromeres are split and tension is lost at anaphase onset? Aurora B kinase, the catalytic subunit of the chromosomal passenger protein complex (CPC) [7], acts as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 29 publications
3
92
0
4
Order By: Relevance
“…37 A high level of Aurora B protein expression can lead to a failure in relocation. AURORA B was among numerous cell cycle regulators that have been identified as EWS/FLI1 target genes, and AURORA B mRNA is upregulated in Ewing sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…37 A high level of Aurora B protein expression can lead to a failure in relocation. AURORA B was among numerous cell cycle regulators that have been identified as EWS/FLI1 target genes, and AURORA B mRNA is upregulated in Ewing sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…10,14,15 Here, we measured the translocation of a fluorescently-tagged version of the Aurora B-binding chromosomal passenger protein INCENP. In control cells, all INCENP-EGFP translocated from the DNA toward the midzone 10-15 min after sister chromatid separation (Fig.…”
Section: B1 Expressionmentioning
confidence: 99%
“…The problem appears to be avoided by the timely inactivation of Cdk1 prior to anaphase, in metaphase. [10][11][12][13][14][15] It is unknown at the moment whether the anaphase problem could occur naturally, or may contribute to aneuploidy in cases when Cdk1 regulatory factors are abnormally expressed. How inactivation of Cdk1 prevents the anaphase problem is also still largely unclear.…”
mentioning
confidence: 99%
“…petronczki's lab anchored aurora B to centro meres, thereby preventing its relo calization at anaphase onset. they found that this recruits a subset of Sac proteins to anaphase kinetochores (Vázqueznovelle & petronczki, 2010). taken together, these results suggest that cpc relocation removes the tension sensor from kinetochores to inactivate the checkpoint, thereby prevent ing its reengagement when tension is lost in anaphase.…”
mentioning
confidence: 60%